2010
DOI: 10.1111/j.1365-2427.2010.02400.x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating aquatic plant communities in a eutrophic river using hyperspectral and multispectral remote sensing

Abstract: 1. This study evaluates the efficacy of remote sensing technology to monitor species composition, areal extent and density of aquatic plants (macrophytes and filamentous algae) in impoundments where their presence may violate water-quality standards. 2. Multispectral satellite (IKONOS) images and more than 500 in situ hyperspectral samples were acquired to map aquatic plant distributions. By analyzing field measurements, we created a library of hyperspectral signatures for a variety of aquatic plant species, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…Water quality degradation is often associated with the disappearance of aquatic vegetation [4,5] and the increase of algal bloom [6]; thus, aquatic vegetation has been widely used as an indicator of water quality and nutrient loading in aquatic systems [7,8]. The efficient and accurate estimation of the distribution of aquatic vegetation is important for lake and water resource management [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water quality degradation is often associated with the disappearance of aquatic vegetation [4,5] and the increase of algal bloom [6]; thus, aquatic vegetation has been widely used as an indicator of water quality and nutrient loading in aquatic systems [7,8]. The efficient and accurate estimation of the distribution of aquatic vegetation is important for lake and water resource management [3].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional site-specific sampling and analysis are limited in both time and spatial resolution, whereas remote sensing offers a potentially convenient way to assess aquatic vegetation in a synoptic manner [7]. The aquatic vegetation and floating algae are known to be co-existent in many aquatic systems [6,9].…”
Section: Introductionmentioning
confidence: 99%
“…; Tian et al. ; Yang & Everitt ), but processing is time‐consuming, even when small areas are covered (Adam et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…The higher spectral resolution of hyperspectral imagery increases the potential for automated species discrimination (e.g. Hamada et al 2007;Tian et al 2010;Yang & Everitt 2010), but processing is time-consuming, even when small areas are covered (Adam et al 2010). In a direct comparison, aquatic vegetation mapping based on visual interpretation yielded more species-specific information compared to automated classification (Valta-Hulkkonen et al 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies (e.g. Kiage and Walker 2009;Jiang and Huete 2010;Tian et al 2010;Anyamba et al 2001) have shown that NDVI can be a sensitive indicator of presence or absence of vegetation in both aquatic and terrestrial environments. The excellent efficacy of the NDVI for detecting vegetation is attributed to the fact that chlorophyll a in plants absorb red light for photosynthesis and reflect highly in the near infrared wavelengths because of scattering caused by internal leaf structure.…”
Section: The Normalized Difference Vegetation Indexmentioning
confidence: 99%